Prenatal Exposure to PM2.5 and Infant Birth Outcomes: Evidence from a Population-Wide Database - Babak Jahanshahi; Brian Johnston; Duncan McVicar; Mark E. McGovern; Dermot O'Reilly; Neil Rowland; Stavros Vlachos (Institute of Labor Economics (IZA), 2022)
There are growing concerns about the impact of pollution on maternal and infant health. In the UK in 2018, 36% of local authorities had levels of PM2.5 where exposure exceeded the annual level recommended by the World Health Organisation at the time. Using a population database of births in Northern Ireland linked to localised geographic information on pollution in mothersâ exteuro™ postcodes (zip codes) of residence during pregnancy, we examine whether prenatal exposure to PM2.5 is associated with a comprehensive range of birth outcomes. Overall, we find little evidence that particulate matter is related to worse infant outcomes once we implement a fixed effects approach that accounts for time-invariant factors common to mothers. While reducing pollution remains an urgent public health priority, our results imply that improvements in short-run levels of prenatal PM2.5 exposure are unlikely to be sufficient by themselves to reduce disparities in birth outcomes.
Keywords: I10; J10; Q53; 330; sibling fixed-effects; infant outcomes; PM2.5; pollution; birth weight